The Perfect Storm: Rapid Progression of Diabetic Ketoacidosis in Pediatric Diabetes in the Setting of COVID-19 - Modarelli, Rachel (J Endocr Soc, 2021)
Introduction: The COVID-19 pandemic has introduced countless challenges to the medical field and has brought increased attention to pediatric patients with pre-existing diagnoses such as diabetes. While pediatric patients have lower rates of COVID-19 mortality, the presence of pre-existing conditions can heighten the severity of their clinical presentation. Here we discuss how COVID-19 may contribute to the pathophysiology of DKA. Case Presentation: Our patient is a 6-year old female with known type 1 diabetes for 6 months, with positive GAD 0.25 nmol/L, c-peptide 0.3 ng/ml, blood glucose 555 mg/dl, HbA1c 10.9, beta hydroxybutyrate (βOHB) 3.21mmol/l, pH 7.35, HCO3 21 mEq/L at her initial presentation, and insulin requirement <0.5 IU/kg/day (in honeymoon). She presented to an outside hospital due to acute onset of abnormal breathing and altered mental status. The day prior, she had one episode of emesis, diarrhea, and abdominal pain, but no fever. She was reported to be agonal breathing with a GCS of 8 and unresponsive to physical or verbal stimuli. She was intubated shortly after arrival and given mannitol. Initial labs included a glucose 486 mg/dL, pH 6.88, bicarbonate 4 mEq/L, lactate 5.8 mmol/L, βOHB 11.9 mmol/L, and anion gap 29 mEq/L, all consistent with severe DKA. With a known family member with COVID-19, she was tested and found to be COVID-19 positive. She was transferred via flight to a higher level of care. Remarkably, she was appropriate for extubation the following day with return to her baseline mental status with improved acidosis. On day three of hospitalization, she developed further COVID-19 symptoms which included sore throat, productive cough, fatigue, headache, and high fever. These symptoms persisted four more days until she was afebrile and discharged home in good condition. Conclusion: Our patient’s rapid progression and severity of illness, including the need for intubation, requires the discussion of how COVID-19 might affect diabetes and suggests opportunities for improvement in clinical practice in children with preexisting diabetes. 1) COVID-19 might change the underlying pathophysiology and cause severe metabolic complications. Possible mechanisms might include a) binding to angiotensin-converting enzyme 2 (ACE2) receptors, which are expressed in key metabolic organs and tissues, including pancreatic beta cells, leading to insulin resistance and islet cell destruction b) enabling a proinflammatory “cytokine storm” in the setting of higher basal proinflammatory state from diabetes. Additionally, ketoacidosis and altered mental status have been discovered in patients with COVID-19 without diabetes, which could potentiate the symptoms of DKA. 2) Prompt recognition and treatment of DKA is warranted as caregivers may attribute the symptoms to COVID-19 rather than DKA and recognition could be too late if symptoms are as acute as described in this case report.